Understanding and managing cancer‐related weight loss and anorexia: insights from a systematic review of qualitative research. Issue 1 (31st March 2015) - Cooper, Christine; Burden, Sorrel T.; Cheng, Huilin; Molassiotis, Alex
Abstract: The aim of this study was to summarize the existing qualitative literature in order to develop the evidence base for understanding and managing weight loss and anorexia, in order to make recommendations for clinical practice. A systematic search was performed to retrieve English language studies using electronic search and manual checks of selected reference lists. Keywords included qualitative, cancer cachexia, weight loss, anorexia, appetite, malnutrition, food, eating, and drinking. The selection and appraisal of papers were undertaken by two reviewers. Twenty‐one qualitative articles were included in the review. There were three major findings emerging from the previous qualitative studies including 'the multidimensionality of weight loss and anorexia experience', 'patients and caregivers' responses to coping with weight loss and anorexia', and 'clinical assessment and management of weight loss and anorexia'. The literature review revealed the multidimensional nature of cachexia and weight loss experience by patients and caregivers, which was not recognized and adequately managed by healthcare professionals. Future research in this area would be helpful in enabling a deeper understanding of the complexity of cachexia and weight loss experience in order to move forward to develop an optimal model of supportive care for patients and caregivers.